How Far Do Membrane Potentials Extend in Space Beyond the Membrane Itself? - Ward, K; Dickinson, E; Compton, R (2010)
The dynamic Nernst-Planck-Poisson equations are used to describe a model system in which an infinitesimal partially permeable membrane separates two different ionic solutions which extend freely in either direction. The spatial extent of the resulting potential difference is assessed, and we demonstrate that non-zero electric field may extend several nanometres into solution, outside the membrane itself. This latter effect is not considered by traditional theories of membrane potentials. © 2010 by ESG.